Inhibition of Toxoplasma gondii Growth by Dihydroquinine and Its Mechanisms of Action - Huffman, Aarin M.; Ayariga, Joseph A.; Napier, Audrey; Robertson, Boakai K.; Abugri, Daniel A. (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii (T. gondii) is a zoonotic parasite that infects the brain of humans and causes cerebral toxoplasmosis. The recommended drugs for treatment or prophylaxis of toxoplasmosis are pyrimethamine and sulfadiazine which have serious side effects. Other drugs available for toxoplasmosis are poorly tolerated. Dihydroquinine (DHQ), is a compound closely related to quinine-based drugs that have been shown to inhibit Plasmodium falciparum, Plasmodium berghei in addition to its anti-arrhythmia properties. However, little is known about the effect of DHQ in T. gondii growth, and its mechanism of action in vitro. In this study, we report the anti-Toxoplasma and anti-invasion properties of DHQ. DHQ significantly inhibited T. gondii tachyzoites growth with IC50s values of 63, 68 and 1.37 nM at 24, 48 and 72 hours, respectively. Under similar conditions, sulfadiazine (SZ) and pyrimethamine (PY) considered as the golden standard drugs for treatment of toxoplasmosis had IC50s values of 1.29, 1.55, 0.95 and 3.19, 3.52 and 2.42 µM, respectively. The rapid dose-dependent inhibition of T. gondii tachyzoites by DHQ compared to the standard drugs (SZ, and PY) indicate that DHQ has high selective parasiticidal effects against tachyzoites proliferation. Remarkably, DHQ had an excellent selectivity index (SI) of 149, 357-fold compared to 24 and 143-fold for PY and SZ, respectively using fibroblast cells. In addition, DHQ disrupted T. gondii tachyzoites mitochondrial membrane potential and elicited high reactive oxygen species generation (ROS). Taken all these findings together, DHQ promises to be an effective and safe lead for the treatment of toxoplasmosis.